Przedsiębiorstwo publiczne w ujęciu teorii praw własnościowych - Tittenbrun, Jacek (Wydział Prawa i Administracji UAM, 1996)
On the basis of its main theoretical premise: that the form of ownership makes a difference for economic performance because its imposes a system of ownership-specific incentives, the property rights theory argues that the fundamental difference in ownership rights between the public and private sectors lies in the inability of a public owner to sell his share of public ownership, and, consequently, the relationship between one person's wealth and his activities is much weaker under public ownership. As a consequence, the incentive of any individual public owner to monitor the behaviour of decision makers in public enterprises is weaker as compared with the incentive in private firms. The dissipation of value through slack attention and other job-related perks is therefore a characteristic phenomenon in the public sector. In addition, efficiency incentives for public enterprise managers are bound to be feeble due to the difficulty in linking their compensation to financial performance. However, there is little evidence to suggest a correlation between share prices and performance of companies. The argument of the property rights theory bases on the role of the capital market. In a number of highly successful, advanced market economies (such as Japan or Germany), however, both the stock market and the mechanism of hostile takeovers play a relatively minor role as instruments of monitoring the managers by shareholders. These models of market economy are not far from the model of efficient bureaucratic control exercised by the state. More broadly, it might be argued that separation of ownership from control (and management) is just as advanced in largely privately owned corporations as in public enterprises.
Public enterprise in the light of the property rights theory